2018
DOI: 10.1371/journal.pgen.1007420
|View full text |Cite|
|
Sign up to set email alerts
|

Within-patient mutation frequencies reveal fitness costs of CpG dinucleotides and drastic amino acid changes in HIV

Abstract: HIV has a high mutation rate, which contributes to its ability to evolve quickly. However, we know little about the fitness costs of individual HIV mutations in vivo, their distribution and the different factors shaping the viral fitness landscape. We calculated the mean frequency of transition mutations at 870 sites of the pol gene in 160 patients, allowing us to determine the cost of these mutations. As expected, we found high costs for non-synonymous and nonsense mutations as compared to synonymous mutation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 68 publications
3
42
0
Order By: Relevance
“…The A49P, M50I, V54I, L68I/V, L74I/M, T97A, S119R, V151I, M154I, K156N, E157Q, K160N, G163K/R, V165I, I203M, S230N, and D232N mutations were observed with a frequency above 1% in at least one subtype. 7 subtypes (49,54,74,92,118,148,153,157,160,170, and 263), 9 positions showed a consensus among 6 subtypes observed (68, 95, 119, 128, 140, 147, 156, 165, and 166), and, finally, 5 positions (114, 125, 151, 163, and 232) showed a consensus at 5 subtypes. These results illustrate well the extent of relevant integrase diversity within and between subtypes, encompassing varied entropy, resistance mutations, and codon predominance.…”
Section: Figmentioning
confidence: 82%
“…The A49P, M50I, V54I, L68I/V, L74I/M, T97A, S119R, V151I, M154I, K156N, E157Q, K160N, G163K/R, V165I, I203M, S230N, and D232N mutations were observed with a frequency above 1% in at least one subtype. 7 subtypes (49,54,74,92,118,148,153,157,160,170, and 263), 9 positions showed a consensus among 6 subtypes observed (68, 95, 119, 128, 140, 147, 156, 165, and 166), and, finally, 5 positions (114, 125, 151, 163, and 232) showed a consensus at 5 subtypes. These results illustrate well the extent of relevant integrase diversity within and between subtypes, encompassing varied entropy, resistance mutations, and codon predominance.…”
Section: Figmentioning
confidence: 82%
“…CpG dinucleotides are suppressed throughout the HIV-1 genomic RNA (gRNA), and introducing CpGs into gag or env inhibits viral replication (12)(13)(14)(15)(16). Furthermore, analysis of clinical HIV-1 samples found that mutations that create new CpG dinucleotides in HIV-1 are twice as costly as those that do not and that increased CpG dinucleotide abundance in env may predict disease progression (17,18). There are at least four mechanisms by which CpG dinucleotides could inhibit HIV-1.…”
mentioning
confidence: 99%
“…The samples were cloned and Sanger-sequenced so that we multiple independent viral sequences from each time point. We have previously used part of this dataset to study soft and hard selective sweeps (Pennings et al, 2014) and to study fitness costs of transition mutations (Theys et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Drug resistance in HIV provides great examples of evolutionary phenomena such as selective sweeps (Messer and Neher, 2012;Pennings et al, 2014), standing genetic variation (Li et al, 2011;Paredes et al, 2010;Pennings, 2012) and mutation-selection balance (Theys et al, 2018;Zanini et al, 2017). Even though HIV has been the subject of intensive research and studied by evolutionary biologists for decades, we are still often limited by the availability of high-quality data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation